Proposta de um método para a definição de rotas cicláveis em áreas urbanas - Kirner, Janice (2006)
Urban problems caused by transportation planning that prioritizes the use of the automobile indicate the inclusion of the bicycle as a viable alternative of urban transport in Brazilian cities. However, it is verified the lack of guidelines that can lead to policies that encourage bicycle transportation, amongst which stands out the insertion or improvement in the infrastructure for cycling. The objective of this study is to propose a method for the definition of cycling routes in urban areas which would have satisfactory results in encouraging bicycle transportation, focusing on the aspects of demand and bicycle level of service in shared roads in urban areas. The proposed method includes the following steps: (1) identification of the potential facility for bicycle trip generation; (2) data collection on the trip behavior of the facility users; (3) identification of the road segments with greater potential demand for bicycle trips; (4) level of service evaluation of the selected road segments; and (5) selection of road segments with greater need of improvement to define cycling routes. A study case was carried out in the city of São Carlos, where the proposed methodology was applied in two utilitarian bicycle trip generation facilities. The necessary data for the study was obtained through 106 interviews, which included a questionnaire and a stated preference survey. The data obtained in the stated preference survey revealed that the pavement condition was the most important attribute in the group s opinion, in comparison to motorized vehicles speed and travel time. The identification and the study of the road segments with greater potential demand for bicycle trips included the demarcation of the influence area of the trip generation facility, the definition of the desire lines and the inventory of the itineraries covered by the interviewed group. These steps were developed with the use of TransCAD. The evaluation of the level of service of the selected segments resulted in measures of level of service with the same value for all of the roads, which did not allow us to prioritize the segments with greater need of improvement to define cycling routes. However, since the values attributed to the road segments were considered unacceptable for bicycle transportation, a series of improvements were suggested to reduce their deficiencies.